Leishmaniasis Trends in Epidemiology, Diagnosis and Treatment - Claborn, David M. (IntechOpen, 2014)
Of all the parasitic diseases, leishmaniasis is one of the most diverse, with a variety of manifestations, from relatively minor cutaneous lesions to deadly visceral infections. It is also widespread, causing human disease in the Americas, Asia, Europe and Africa. The environments in which this disease occurs range from desert to tropical jungle to urban habitats. Not surprisingly, the literature on this disease is written in a variety of languages including Portuguese, Arabic, English and French among others. This book provides a synopsis in English of much of the recent research on leishmaniasis, with a focus on the epidemiology, diagnosis and treatment of the disease as described by researchers around the world, but with a focus on the research from Brazil and the Middle East.